Effectiveness of Discovery Learning-Based Practical Activities on Students' Critical Thinking Abilities and Scientific Attitudes - Reza Wulandari; Siti Darwa Suryani; Rizki Pratama (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to determine whether there is an influence of practical activities on students' critical thinking skills and scientific attitudes. The study was conducted in June-July 2025, the method used in this study is quantitative quasi-experimental. Sampling was carried out non-randomly using purposive sampling techniques. The sample of this study was 27 second semester students. The average value of critical thinking skills was 82.22 while the average value of the scientific attitude posttest was 67.48. The average value of critical thinking skills and scientific attitudes was obtained from the calculation of prerequisite tests, namely the normality test and the homogeneity test. Furthermore, a t-test was carried out is using the Paired Samples Test. The results of the Paired Samples Test were 0.000 because the p value <0.05, it can be concluded that there is an influence of discovery learning-based practical activities on students' critical thinking skills and scientific attitudes